Development of infographic as a warning for the prevention of penile cancer in Maranhão - Maria Muniz Lobo, Letícia; Carolina Garcia Ribeiro, Ana; Isabelle Silveira da Silva, Maria; Kareen Conceição Mendes, Nicole; Flávia de Albuquerque Campos, Livia (InfoDesign, 2022)
It is important to talk about prophylactic measures for the intimate health of men when observing the high incidence of penile cancer in Maranhão, mostly caused by poor hygiene and little access to information. An interview was carried out to identify the most effective way to present information. The results culminated in a proposal that considers factors that influence the perception and absorption of the content so that the message can be received and understood more efficiently by the interlocutors through the use of information design resources.